2018
DOI: 10.1007/s11250-018-1602-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for clinical ketosis and association with milk production and reproduction variables in dairy cows in a hot environment

Abstract: The aims of the present study were to investigate (1) the risk factors that influence the occurrence of clinical ketosis (CK; blood β-hydroxybutyrate > 3.0 mmol/L) and (2) to determine the influence of subclinical ketosis (SCK; 1.2 ≤ β-hydroxybutyrate ≤ 2.9 mmol/L) and CK on reproductive performance and milk yield in high-yielding Holstein cows in a hot environment. Cows (n = 345) were blood sampled from 6 to 15 days postpartum for β-hydroxybutyrate (BHB) determination with a hand-held meter. Cows calving in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…Although circulating ketone bodies can be used to a certain extent as energy source by mammary tissue and other organs, excessive blood ketone bodies negatively affect the reproduction function. In line with the results of the present study, Rutherford et al (2016) and Mellado et al (2018b) also found that low blood BHBA levels shortly after calving had a positive effect on the establishment of pregnancy at first service.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although circulating ketone bodies can be used to a certain extent as energy source by mammary tissue and other organs, excessive blood ketone bodies negatively affect the reproduction function. In line with the results of the present study, Rutherford et al (2016) and Mellado et al (2018b) also found that low blood BHBA levels shortly after calving had a positive effect on the establishment of pregnancy at first service.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, high serum BHBA concentrations were associated with a higher number of services per conception, which is in line with other studies with dairy cows experiencing ketosis shortly after calving (Gillund et al, 2001;Mellado et al, 2018b). Considering de AUC (0.64), blood BHBA concentrations one-week post-calving presented a moderately accurate discriminating ability for cows requiring more than two services to become pregnant.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, numerous publications reported the association of ketosis and fertility traits in dairy cows. One study found that circulating BHBA was increased the conception rate at first service and fetal loss was decreased in cows [15], and the calving-to-first-service interval and the calving-to-conception interval were prolonged with subclinical ketosis [16]. It was also found that a combination of NEB and reduced dry matter intake reduced fertility and milk production in dairy cows [17].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies report a negative association between high ketosis incidence and high ambient temperature-humidity index 87 at calving or high temperature 79 at calving, respectively. This contradicts our findings, which show an association of high mean yearly temperature (OR=1.23 [1.11; 1.35]), temperature deviation (Or=1.89 [1.71; 2.09]) and high mean relative humidity (OR=1.39; 1.26; 1.54) with increased clinical ketosis risk.…”
Section: Resultsmentioning
confidence: 99%